Perfectionism and psychological well-being in adolescents with high intellectual abilities - M. Rosa Sánchez-Moncayo; Inmaculada Menacho; Pedro Ramiro; José I. Navarro (Frontiers in Psychology, 2025)
IntroductionPerfectionism is understood as a psychological construct that can either facilitate excellence in various areas of life or lead to maladaptation when not properly managed. Although numerous studies exist on perfectionism and high abilities, this relationship still has many unresolved scientific questions, especially regarding the emotional development of individuals.MethodThis study aimed to analyze the relationship between perfectionism and psychological well-being in 103 adolescents aged 12 to 17 years with either high intellectual abilities or average intellectual capacity. Subgroups were established based on different age ranges to compare the relationships between perfectionism and psychological well-being throughout adolescence.ResultsThe results showed statistically significant differences in the mean levels of perfectionism according to the subjects’ intellectual abilities, with the mean being higher in the high intellectual ability groups. However, there was no statistically significant correlation between perfectionism and psychological well-being in any of the groups, regardless of intellectual capacity or age. Although adaptive perfectionism was more common in adolescents with high abilities, this did not necessarily translate into higher levels of psychological well-being.Discussion and conclusionThe study highlights the complex relationship between high intellectual ability (HIA) and perfectionism, distinguishing between adaptive and maladaptive forms. While HIA adolescents show higher perfectionism levels, their psychological well-being remains comparable to peers. Findings emphasize the role of educational and cultural contexts, urging tailored interventions to foster adaptive perfectionism and mitigate its negative effects.